Influence of reaction heat on time dependent processes in a chemically reacting binary mixture - Marques Júnior, Wilson (2012)
In this paper we study time dependent problems, like the propagation of sound waves or the behavior of small local wave disturbances induced by spontaneous internal fluctuations, in a binary mixture undergoing a chemical reaction of type A+A= B+B. The study is developed at the hydrodynamic Euler level, in a chemical regime of fast reactive process in which the chemical reaction is close to its final equilibrium state. The hydrodynamic state of the mixture is described by the balance equations for the mass densities of both constituents A and B, together with the conservation laws for the momentum and total energy of the mixture. The progress of the chemical reaction is specified by an Arrhenius-type reaction rate which defines the net balance between production and consumption of each constituent. Assuming that the considered time dependent problems induce weak macroscopic deviations, the hydrodynamic equations are linearized through a normal mode expansion of the state variables around the equilibrium state. From the dispersion relation of the normal modes, we determine the free and forced phase velocities as well as the attenuation coefficients of the waves. We show that the dispersion and absorption of these waves depend explicitly on the heat of the chemical reaction, the concentrations of the constituents and the activation energy through the exponential factor of Arrhenius law.